Unequal Chances on a Flexible Labor Market, The Case of the Netherlands - Govert E. Bijwaard; Justus Veenman (Tinbergen Institute, 2008)
Labor markets in Western countries are becoming more and more flexible, thereby meeting the needs of employers. Yet the new flexibility also offers opportunities to workers, while at the same time bears the risk of long-term exclusion. This paper deals with unequal chances on the contemporary Dutch labor market, in particular for workers with unfavorable human capital characteristics. As such we have chosen workers from the four largest immigrant groups: Turks, Moroccans, Surinamese and Antilleans. The data used are from the SPVA, the survey 'Social Position and Use of Public Utilities by Migrants' for the years 1998 and 2002. These are based on stock sampling. Since for some individuals labor market transitions occur at a very low rate, these individuals may stay in the current state till they reach the retirement age of 65. We estimate hazard rate models that account for both the stock-sampling and the possible maximum duration for the transitions from unemployment, household care and disability to employment. Then we decompose the differences in expected duration between the immigrant groups and the Dutch natives into the contribution of differences in observable characteristics, coefficient estimates and baseline hazard parameters. The main results of the analyses are that unequal chances exist, but to a different degree for the various groups and with variations per transition type. Labor market experience seems to protect from long-term exclusion.
Keywords: C41; J64; J7; 330; Flexible labor market; duration; Oaxaca-Blinder decomposition; Arbeitsmarktpolitik; Arbeitsmarktdiskriminierung; Arbeitsmarktflexibilität; Ethnische Diskriminierung; Niederlande